Eighteen tides and a tiger - Basu, Anjana (New Delhi Teri Press, 2020)
The Sunderbans, a tangle of forests where, according to legend, ghost tiger roar at the dead of night making the mangroves shiver. However, the tiger Rohan finds is real and needs to be rescued. Rohan, on his first internship, is lost in the middle of this haunted land very unlike the hilly Corbett country he is familiar with. And he needs to be rescued too. Help comes in the shape of a girl who never seems to turn a hair at tigers or marshes! And as always, there is a mystic presence close at hand. Rohan heard a murmur of, (3z(BMama!(3y (Band one or two of the sailors started rocking back and forth themselves in a kind of prayer. He looked wordlessly at the sailor next to him, whose fingers were tight around his clay pot of tea. (3z(BBagh,(3y (Bthe sailor whispered. (3z(BTiger!(3y (BThe top deck continued to rock in a steady kind of motion as if something might be pacing up and down on it. There was another tiger. It appeared like a streak of fire out of the scrub trees springing past Rohan$1 (Bs shoulder, so close that he felt the heat of the big body and its scent filled his nostrils. It had missed him because he had been bending... Uniting pace, a symbol of courage and along with that a character from a fairy tale to link old and new, So that a bridge is formed between the heroic, romantic traditions of the past and today$1 (Bs modern world. Rituparno Ghosh, film makers
Keywords: Asia-Sundarbans; English Fiction